PERSEPSI MASYARAKAT HUKUM ADAT TERHADAP KEBERADAAN HUTAN DI KASEPUHAN KARANG DAN CISUNGSANG, KABUPATEN LEBAK, BANTEN - Surati Surati; Sylviani Sylviani; Niken Sakuntaladewi; Dian Charity Hidayat; Kuncoro Ariawan (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2021)
The existence of customary territories, which are generally located in forest areas, create a separate conflict. One solution is the granting of customary forest management rights to customary law communities (CLC), and there are common understanding and perception between community and forest area managers. The study aims to understand perceptions of CLC about their needs and interests in forests. The research was conducted in Kasepuhan Karang and Cisungsang. Research method is descriptive qualitative. Data processing was done in a tabulated form and analyzed descriptively. The results showed that the perceptions of CLC Kasepuhan Karang and Cisungsang on customary forest management in terms of social, economic, and ecological aspects were generally positive, and that the condition of the Kasepuhan Karang forest is better. It was found that the ranges from social aspects are 45%-95%, economic aspects are 39%-100%, and ecological aspects are75%-100%. They depend on the forest as a source of life, medicines, and handicraft materials. Forests are also a place for customary rituals, a source of food, a source of water that is preserved and passed down from generation to generation. Customary institutions need to be strengthened with the active participation of traditional elders or the younger generation, so that future generations understand and inherit customary culture values.